2019
DOI: 10.1029/2018jb016903
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Deformation Behavior of Synthetic Polycrystalline Magnetite

Abstract: We performed a series of deformation experiments on synthetic magnetite aggregates to characterize the high‐temperature rheological behavior of this mineral under nominally dry and hydrous conditions. Grain growth laws for magnetite were additionally determined from a series of static annealing tests. Synthetic magnetite aggregates were formed by hot isostatic pressing of fine‐grained magnetite powder at 1,100 °C temperature and 300‐MPa confining pressure for 20 hr, resulting in polycrystalline material with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
1
7
1
Order By: Relevance
“…Their activation energy of 307 is somewhat lower than our observed values, but is reasonably close considering the different sample sources and experimental apparatus used. It is also worth noting that the strength of magnetite aggregates studied by Till et al (2019) is closest to those of the harder magnetite single-crystal orientations found in this study. Experimentally determined creep rates for polycrystalline hematite by Siemes et al (2003) are comparable to our data for ilmenite compressed perpendicular to <c> (experiment KI05) but with a lower activation energy of 225 kJ/mol.…”
Section: Effect Of Loading Direction and Comparison To Creep Of Polycsupporting
confidence: 76%
See 4 more Smart Citations
“…Their activation energy of 307 is somewhat lower than our observed values, but is reasonably close considering the different sample sources and experimental apparatus used. It is also worth noting that the strength of magnetite aggregates studied by Till et al (2019) is closest to those of the harder magnetite single-crystal orientations found in this study. Experimentally determined creep rates for polycrystalline hematite by Siemes et al (2003) are comparable to our data for ilmenite compressed perpendicular to <c> (experiment KI05) but with a lower activation energy of 225 kJ/mol.…”
Section: Effect Of Loading Direction and Comparison To Creep Of Polycsupporting
confidence: 76%
“…The activation energies determined here for magnetite single crystals are notably lower than that reported for dislocation creep of dry polycrystalline magnetite by Till et al (2019) of 463 ± 19 kJ/mol. The discrepancy partly arises from the different oxygen fugacity buffers imposed by the Ni-NiO jacket used in the Paterson rig by Till et al (2019) and the CO 2 -H 2 mixture used in the creep rig here. When both sets of data are plotted at the experimental buffers, creep rates are similar at high temperatures but differ significantly at low temperature (Fig.…”
Section: Effect Of Oxygen Fugacity On Dislocation Creep Rates In Magncontrasting
confidence: 76%
See 3 more Smart Citations